Korelasi Metakognitif dengan Retensi Belajar Siswa SMA Negeri di Kabupaten Rote Ndao Nusa Tenggara Timur - Sudirman, Sudirman; Yusnaeni, Yusnaeni (LPPM Universitas Negeri Jakarta, 2022)
This study aims to obtain an initial mapping of metacognitive abilities, student chemistry retention, metacognitive contribution to chemical retention of state high school students in Rote Regency. The population of this research is the XII IPA grade students of State Senior High Schools in Rote Ndao Regency, NTT. A sample of 200 students from 9 study groups was determined by simple random sampling technique. The research instrument was a Metacognitive Awareness Inventory (MAI) questionnaire, for students' metacognition, and a test for students' chemical retention. Data analysis used descriptive and inferential statistical techniques. The results of the analysis obtained: 1) the average knowledge and metacognitive regulation of Rote Ndao High School students is in the sufficient category while the average learning retention is in the medium category, 2) the percentage of good categories for metacognitive knowledge and regulation is 52.50%, respectively. and 58%, 3) the highest percentage of chemical retention in the low category was 46.50%, 4) metacognitive knowledge and cognitive regulation with chemical retention were positively correlated with a reliability value of 13.4%. The results of the study indicate that there is a relationship between knowledge and metacognitive regulation with chemical retention of class XII IPA students of SMA Negeri in Rote Ndao Regency, East Nusa Tenggara. KeywordsMetacognitive, Metacognitive Knowledge, Metacognitive Regulation, Learning Retention